Functional analysis of limb transcriptional enhancers in the mouse. Issue 4 (11th June 2014) - Nolte, Mark J.; Wang, Ying; Deng, Jian Min; Swinton, Paul G.; Wei, Caimiao; Guindani, Michele; Schwartz, Robert J.; Behringer, Richard R.
SUMMARY Transcriptional enhancers are genomic sequences bound by transcription factors that act together with basal transcriptional machinery to regulate gene transcription. Several high‐throughput methods have generated large datasets of tissue‐specific enhancer sequences with putative roles in developmental processes. However, few enhancers have been deleted from the genome to determine their roles in development. To understand the roles of two enhancers active in the mouse embryonic limb bud we deleted them from the genome. Although the genes regulated by these enhancers are unknown, they were selected because they were identified in a screen for putative limb bud‐specific enhancers associated with p300, an acetyltransferase that participates in protein complexes that promote active transcription, and because the orthologous human enhancers (H1442 and H280) drive distinct lacZ expression patterns in limb buds of embryonic day (E) 11.5 transgenic mice. We show that the orthologous mouse sequences, M1442 and M280, regulate dynamic expression in the developing limb. Although significant transcriptional differences in enhancer‐proximal genes in embryonic limb buds accompany the deletion of M1442 and M280 no gross limb malformations during embryonic development were observed, demonstrating that M1442 and M280 are not required for mouse limb development. However, M280 is required for the development and/or maintenance of body size; M280 mice are significantly smaller than controls. M280 also harbors an "ultraconserved" sequence that is identical between human, rat, and mouse. This is the first report of a phenotype resulting from the deletion of an ultraconserved element. These studies highlight the importance of determining enhancer regulatory function by experiments that manipulate them in situ and suggest that some of an enhancer's regulatory capacities may be developmentally tolerated rather than developmentally required.